Improving Creative Thinking Through Creative Responsibility Based Learning (CRBL) Model - Agustiana, I. G. A. T.; Tika, I Nyoman; Wibawa, Made Citra (International Journal of Elementary Education, 2021)
The use of various models and approaches still shows that students have difficulties understanding science content. This obstacle causes psychological barriers for students, so creative thinking skills are needed. The purpose of this study is to analyze the differences in creative thinking skills between students who follow the Creative Responsibility Based Learning (CRBL) learning model and students who follow the conventional learning model in terms of students' self-efficacy in learning science. This type of research is an experimental study with a Non-Randomized Post-test Only Control Group Design. In this design, the subject is not taken randomly. The number of population members is 184 students. The techniques used to analyze the data are qualitative descriptive analysis, quantitative, and inferential statistics. The result of the research is that the science learning outcomes of students who follow the CRBL learning model are higher than students who follow the conventional learning model with a significance value of 0.044 < 0.005. There is a difference in creative thinking ability between fourth grade elementary school students who have high self-efficacy and low self-efficacy in science learning with a significance value of 0.00 <0.05). There is a significant interaction effect between the learning model and self-efficacy on students' creative thinking skills with a significance value of 0.00 < 0.05). It can be concluded that this learning model provides direct learning experiences to students in building self-efficacy and creative thinking skills in learning basic science concepts so that teachers can apply them.